Body weight changes, haematological and serum biochemical indices of West African (WAD) Dwarf rams fed ammonium sulphate fortified diets (2017)
Weight gain, haematology and serum biochemical parameters of sixteen (16) West African Dwarf (WAD) rams weighing 12.8+0,12 kg were assigned to diets containing 0g/kg, 2.5g / kg, 5.0g/kg and 7.5g/kg levels of ammonium sulphate ((NH4)2SO4) as T0, T2.5, T5.0 and T7.5, respectively. The animals were fed the diet and wilted guinea grass in a 60:40. Daily weight gain, feed conversion ratio, platelet, lymphocytes, neutrophil, cholesterol, Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline Phosphatase (ALP) values of the rams fed ammonium sulphate fortified diets were significantly (p<0.05) higher than the control. Haemoglobin concentration increased in ramsfed ammonium sulphate fortified diets from 14.00-14.68% compared to control. The white blood cell (x 10(6)/mm(3)) varied from T0 (4.3 I) to T7.5(5.15). The lowest packed cell volume (41.00%) was obtained for rams on control diet. Red blood cell (x 10(6)/mm(3))) ranged from T0 (11.86) to T7.5 (13.02) while alanine aminotransferase (ALT) ranged from 10.25 (T0) to 25.25 (T7.5) (x 10(6)µL). The study revealed that inclusion of ammonium sulphate fortified diets of WAD rams up to 7.5g/kg had no deleterious effects on weight gain, haematological and serum indices of WAD rams